relation between G and the change of C will be derived for a plate with an edge

# Relation between g and the change of c will be

This preview shows page 37 - 41 out of 163 pages.

relation betweenGand the change ofCwill be derived for a plate with an edge crack, whichis loaded by a forceFin pointP. When the crack length increases fromatoa+da, twoextreme situations can be considered :fixed grips: pointPis not allowed to move (u= 0),constant load: forceFis kept constant.PFuFua+daaPFig. 4.4 :Edge crack in a plate loaded by a forceF. 28 a a a + da a + da F F u u dU i dU i dU e Fig. 4.5 : Internal and external energy for fixed grips (left) and constant load (right). 4.4.1 Fixed grips Using the fixed grips approach, it is obvious that dU e = 0. The force F will decrease ( dF < 0) upon crack growth and the change of the internally stored elastic energy can be expressed in the displacement u and the change dF . The energy release rate can be calculated according to its definition. fixed grips : dU e = 0 dU i = U i ( a + da ) U i ( a ) ( < 0) = 1 2 ( F + dF ) u 1 2 Fu = 1 2 udF Griffith’s energy balance G = 1 2 B u dF da = 1 2 B u 2 C 2 dC da = 1 2 B F 2 dC da 4.4.2 Constant load With the constant load approach, the load will supply external work, when the crack propa- gates and the point P moves over a distance du . Also the elastic energy will diminish and this change can be expressed in F and du . The energy release rate can be calculated according to its definition. constant load dU e = U e ( a + da ) U e ( a ) = Fdu dU i = U i ( a + da ) U i ( a ) ( > 0) = 1 2 F ( u + du ) 1 2 Fu = 1 2 Fdu  30 a F 2 h u B F u Fig. 4.7 : Beam with a central crack loaded in Mode I. u = Fa 3 3 EI = 4 Fa 3 EBh 3 C = Δu F = 2 u F = 8 a 3 EBh 3 dC da = 24 a 2 EBh 3 G = 1 B bracketleftbigg 1 2 F 2 dC da bracketrightbigg = 12 F 2 a 2 EB 2 h 3 [J m 2 ] G c = 2 γ F c = B a radicalBig 1 6 γEh 3 The question arises for which beam geometry, the energy release rate will be constant, so no function of the crack length. It is assumed that the height of the beam is an exponential function of a . Applying again formulas from linear elastic beam theory, it can be derived for which shape G is no function of a . a h Fig. 4.8 : Cracked beam with variable cross-section. C = Δu F = 2 u F = 8  #### You've reached the end of your free preview.

Want to read all 163 pages?

• Fall '19
• Fracture mechanics
• • • 